Memperkuat Semangat Kewirausahaan Pemuda Melalui Peningkatan Kapasitas Organisasi dan Pemanfaatan E-Commerce: (Program Pengabdian Masyarakat di Wiradesa, Pekalongan) - Farida Rohmah; Husni Awali; Singgih Setiawan; Musliha Musliha (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This Community Service Program aims to strengthen the entrepreneurial spirit of the Wiradesa Youth Association through strengthening organizational capacity and utilizing e-commerce as a strategy to increase the independence and economic value of youth organizations. The implementation method includes institutional mentoring, entrepreneurship training, and provision of e-commerce platform usage to support the formation and management of organization-based business units. The results of the activity indicate an increase in organizational capacity in the aspects of governance, understanding of member entrepreneurship, and readiness to develop business units capable of generating added economic value. This program encourages a change in the role of youth organizations from organizations focused on social activities to productive organizations with economic potential and contributing to the welfare of members and the surrounding community. The novelty of this activity lies in the integration of strengthening youth organizations with the development of e-commerce-based digital entrepreneurship as an adaptive and sustainable model for youth empowerment.